2021
DOI: 10.1371/journal.pone.0252965
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulatory effects of repetitive transcranial magnetic stimulation on neural plasticity and motor functions in rats with an incomplete spinal cord injury: A preliminary study

Abstract: We investigated the effects of intermittent theta-burst stimulation (iTBS) on locomotor function, motor plasticity, and axonal regeneration in an animal model of incomplete spinal cord injury (SCI). Aneurysm clips with different compression forces were applied extradurally around the spinal cord at T10. Motor plasticity was evaluated by examining the motor evoked potentials (MEPs). Long-term iTBS treatment was given at the post-SCI 5th week and continued for 2 weeks (5 consecutive days/week). Time-course chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…According to a prior study on healthy rats, MEP can be continually increased for up to 30 min following a single session of iTBS [ 37 ]. A study on an SCI animal model reported the effects of iTBS stimulation on mild and moderate SCI groups’ neuroplasticity, with enhanced MEPs from baseline after week 1 and week 4 stimulation compared to the severe SCI group [ 38 ], which is consistent with our current study results. In our current study, pre- vs. post-week 1 and week 4 also showed a significant increase in post_25 min ( p = 0.012 *) and post_30 min ( p = 0.026 *) MEPs ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…According to a prior study on healthy rats, MEP can be continually increased for up to 30 min following a single session of iTBS [ 37 ]. A study on an SCI animal model reported the effects of iTBS stimulation on mild and moderate SCI groups’ neuroplasticity, with enhanced MEPs from baseline after week 1 and week 4 stimulation compared to the severe SCI group [ 38 ], which is consistent with our current study results. In our current study, pre- vs. post-week 1 and week 4 also showed a significant increase in post_25 min ( p = 0.012 *) and post_30 min ( p = 0.026 *) MEPs ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Differentiating the effect of these stimulation waveforms is very difficult because the sham group also significantly improved its BBB score. In addition, another study previously mentioned that iTBS does not significantly improve BBB scores in mild or moderate SCI animal models [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique operates through its neuromodulatory effects on neuronal circuitry [23,24]. The potential of rTMS to improve outcomes following incomplete SCI has gained recognition in the past few years but has mainly been applied to enhance locomotor recovery [25][26][27] and sensorimotor restoration [27][28][29] in preclinical models of SCI.…”
Section: Introductionmentioning
confidence: 99%